2021
DOI: 10.1017/s0010417520000377
|View full text |Cite
|
Sign up to set email alerts
|

Burying “Zik of Africa”: The Politics of Death and Cultural Crisis

Abstract: This article uses the death and burial of one of the most important political leaders in twentieth-century Africa, and Nigeria's first and only ceremonial president, Rt. Hon. (Dr.) Nnamdi Azikiwe, to reflect on how and why the deaths and burials of significant persons in Africa represent occasions for the (re)production and management of cultural crises. It argues that the extant literature on the death of consequential persons in Africa either understates or overlooks the generalizability of the “essential co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Since the Eyo is also about death and dying, it draws attention to the instrumentality of death and funerals in establishing belonging and ownership in Lagos. There is a body of literature on the politics of funerals in Africa (Smith 2004; Geschiere 2005; Onwuzuruigbo 2014; Adebanwi 2021). This is because interring the dead is an important ritual on the continent.…”
Section: Festivals and Funeral Politics In The City: Rituals Belongin...mentioning
confidence: 99%
See 3 more Smart Citations
“…Since the Eyo is also about death and dying, it draws attention to the instrumentality of death and funerals in establishing belonging and ownership in Lagos. There is a body of literature on the politics of funerals in Africa (Smith 2004; Geschiere 2005; Onwuzuruigbo 2014; Adebanwi 2021). This is because interring the dead is an important ritual on the continent.…”
Section: Festivals and Funeral Politics In The City: Rituals Belongin...mentioning
confidence: 99%
“…Part of the ritual is to bury the dead in their homestead, which signifies and stands as a point of connection between the dead and the living, thereby ensuring the continued presence of the dead 32 . Existing research has shown that being buried ‘at home’ is one of the most common symbolic pointers to the continuation and – to a certain extent – strengthening of ties to the place of origin (Smith 2004; Geschiere 2005; Adebanwi 2021). Smith argues that established cases of elite funerals ‘have brought into view the profound ways in which the political and symbolic dramas that unfold around burials capture many of the dynamics of social change in contemporary Africa’ (2004: 569).…”
Section: Festivals and Funeral Politics In The City: Rituals Belongin...mentioning
confidence: 99%
See 2 more Smart Citations